(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2024)
The research is concerned with how a company’s commitment to environmental and social sustainability practices affects public perception and brand reputation. This study aims to analyze the impact of sustainability policies on brand image in industrial companies, using a scientific methodology that combines quantitative and qualitative methods to obtain comprehensive and accurate results. The methodology includes the steps of research design, data collection, analysis, and providing practical recommendations. The study results show that transparency in presenting and implementing sustainability policies contributes significantly to enhancing trust between consumers and the company. Companies that provide periodic reports and explain their sustainability efforts gain a positive image among the public. Companies that adhere to sustainability principles also enjoy greater customer loyalty. This loyalty is reflected in repeat purchases and recommending the brand to others. It was found that in some cases, there is a gap between the announced sustainability policies and their actual implementation. This disparity negatively affects the brand image, as customers feel that the company is not credible. The study recommended that companies should be transparent in how they implement sustainability policies.